(untitled) (Research, Society and Development, 2020)
Agriculture plays an important role in the delivery of food and other goods involved to consumers and markets, with a large economic participation in Brazil, the agricultural model that has undergone transformations and can cause environmental damage is worthwhile. Thus, before or exposing this article, it seeks to analyze the level of sustainability of agricultural production in different Mesoregions in the State of Paraíba. As for the methodological procedures, the study was carried out with producers in the municipality of Pombal, in the Sertão region and with producers in the municipality of Lagoa Seca, in the Agreste region, in the State of Paraíba, a data collection was carried out using questionnaires for the exclusive use of users and based on these data, the quality of life, social capital and environment indices were calculated, to then calculate the sustainability index and assess the level of sustainability in the two areas of the study. The survey results show that two mesoregions have reached the average level of sustainability. When comparing the indices, it was evident that the quality of life was an indicator that contributed to the equitable way in two areas of study, already in the social capital, it is stronger in the mesoregion of sertão, already in the environmental indicator displayed in larger numbers.